2024
DOI: 10.1021/acs.oprd.4c00021
|View full text |Cite
|
Sign up to set email alerts
|

Highly Productive Flow Synthesis for Lithiation, Borylation, and/or Suzuki Coupling Reaction

Hiroki Soutome,
Kei Maekawa,
Yosuke Ashikari
et al.

Abstract: The efficient synthesis of aromatic boronic acids was achieved by increasing the concentration, flow rate, and mixer diameter to prevent clogging. A 1 h synthesis actually produced 180 g of boronic acid. The real-time analysis of the reaction solution was investigated using in-line analyzers suitable for high flow rates. Additives were also studied to accelerate the Suzuki coupling reaction of the boronic acids. Integrated one-flow reactions combining boronic acid synthesis and Suzuki coupling produced pharmac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…To investigate the effect of mixing on the yield, we evaluated the dependence of the yield on the flow rate (Figure ). A previous study demonstrated that low flow rates resulted in low mixing efficiency and reaction yield. ,, Figure shows a dramatic decrease in the yield of 4a below 8 mL min –1 . HPLC analysis revealed that the low yields were caused by low conversion of the substrates resulting from slow mixing.…”
mentioning
confidence: 99%
“…To investigate the effect of mixing on the yield, we evaluated the dependence of the yield on the flow rate (Figure ). A previous study demonstrated that low flow rates resulted in low mixing efficiency and reaction yield. ,, Figure shows a dramatic decrease in the yield of 4a below 8 mL min –1 . HPLC analysis revealed that the low yields were caused by low conversion of the substrates resulting from slow mixing.…”
mentioning
confidence: 99%